Influence of the CD14 genotype polymorphism on C - reactive protein levels in patients with coronary artery disease - Ahmed Mohamed Taha; Khaled Hussein Mohammed; Mohammed Mohammed Khaled; Sanaa Sayed Abdelshafy (Cairo : Ahmed Mohamed Taha, 2010)
Inflammation is one of the major components of atherosclerosis which is the underlying disorder that leads to various diseases including coronary artery disease (CAD ) . CD14 receptor is an important mediator of inflammatory reactions and its expression is under genetic control . The allelic variant of the the CD14 polymorphism located in the promoter region of the CD14 gene is associated with receptor expression and ischemic risk
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Coronary artery disease; Inflammation; Polymorphism